Video analysis as a biomechanical assessment tool for Nordic walking techniques - Samsonov M.A. ,; Fursov V.V. ,; Kolesnikov N.V. ,; Striga S.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop a scientifically sound method of videography and subsequent analysis of the Nordic walking technique. Methods and structure of the study. A study of Nordic walking techniques was conducted in the athletics arena of St. Petersburg State University named after P.F. Lesgaft with the participation of Irina Markova, the champion of Russia. For a detailed analysis of the movement, small (1 cm in diameter) colored marks were glued to all the joints of the athlete, which are clearly visible on video from different angles. This allowed us to get a complete picture of the movements in all planes. Research results and conclusions. The use of multi‑camera high‑speed video in the study of Nordic walking techniques has shown its practicality and comparative ease in terms of equipment preparation and debugging. An important feature of the process was the increased requirements for the brightness of additional lighting and the need for the coordinated work of two videographers. The video analysis procedure using the Kinovea software required considerable effort, due to the large number of analyzed parameters. However, it provided high accuracy, especially when determining kinematic characteristics (the error in measuring time was 0.002 s, and when measuring spatial parameters – from 0.01 to 0.02 m). The proposed method makes it possible to easily obtain visual illustrative material that displays the movements of an athlete from different angles. These materials can be used both for a detailed analysis of individual techniques and as a demonstration aid in the training of other athletes.